DNA‐based testing in lung transplant recipients with suspected non‐viral lower respiratory tract infection: A prospective observational study. Issue 1 (21st December 2017) - Drick, Nora; Seeliger, Benjamin; Greer, Mark; Bollmann, Benjamin A.; Ziesing, Stefan; Welte, Tobias; Gottlieb, Jens
Abstract: Background: Non‐viral lower respiratory tract infections (LRTI) are common among lung transplant (LTx) recipients with increased mortality. Early pathogen identification is crucial to guide therapy and avoid adverse events. Results from cultures may require up to 72 hours. Multiplex polymerase chain reaction assay (PCR) may allow faster pathogen identification, but its utility in LTx recipients with suspected non‐viral LRTI remains unclear. Methods: In a prospective open‐label observational trial, LTx recipients presenting with suspected LRTI received bronchoscopy with bronchoalveolar lavage (BAL). Samples were simultaneously analyzed by multiplex PCR (Curetis P55 Pneumonia) and cultures for pathogen identification. Time to result notification for PCR and cultures and time to final diagnosis were recorded. Definition of non‐viral LRTI was isolation of a lung‐pathogenic non‐viral pathogen by either method. Results: Forty‐eight patients were included, with 32 (67%) having a lung‐pathogenic isolate by conventional cultures. In 17/32 pathogen identification was identical on PCR, in 12/32 (37%) PCR returned negative, and in 3/32 (10%) PCR and culture identified different pathogens. Sensitivity and specificity with 95% confidence intervals for pathogen isolation for PCR were 66% (47‐81) and 100% (79‐100), respectively. The positive predictive value for PCR was 100% (84‐100) and the negative predictive value was 59% (39‐78). PCR results were available after 21.2 hours (interquartile range [IQR] 19.3‐65.7) vs 23 hours (IQR 21.1‐67.4) from cultures ( P < .0001). The time to final diagnosis of non‐viral LRTI was 22.9 hours (20.4‐37.5). Conclusion: In LTx recipients with suspected non‐viral LRTI, multiplex PCR had a lower sensitivity than cultures. Results were available 2 hours earlier.